Dynamic rheological properties of polyurethane-based magnetorheological gels studied using oscillation shear tests. Issue 18 (1st April 2019) - Zhang, Guang; Wang, Huixing; Wang, Jiong; Zheng, Jiajia; Ouyang, Qing
Abstract : This paper studies the dynamic rheological behaviors of magnetorheological (MR) gels containing different CIP weight fractions suspended in polyurethane (PU). Abstract : This paper studies the dynamic rheological behaviors of magnetorheological (MR) gels containing different CIP weight fractions suspended in polyurethane (PU). The dynamic characteristics of prepared MR gels are obtained using large amplitude oscillation shearing (LAOS). The influence of strain amplitude, applied coil current, CIP weight fraction and driving angular frequency on the dynamic rheological properties of MR gels are systematic discussed. The results demonstrate the onset strain from linear viscoelastic region to non-linear viscoelastic region increases with applied coil current. The maximum loss modulus increases with applied coil current and CIP mass fraction. The larger the coil current and CIP mass fraction, the greater the shear strain corresponding to the maximum value. Microstructural variation of self-assembled copolymer chains and magnetic-induced CIP chains at different strain amplitudes, applied coil currents and CIP weight fractions are proposed as an explanation of the non-linear rheological behaviors of PU-based MR gels.